Drying Cocoa, Trinidad, B.W.I. - No. 27 - (:unkn) unknown (Muir, Marshall and Co., Port of Spain, Trinidad., 2009)
Workers at a cocoa plantation drying the cocoa beans on cocoa houses by walking and turning the beans. This process allows air to flow through the beans to dry them evenly.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cocoa trade--Trinidad and Tobago; Agriculture--Trinidad and Tobago; 1919; Cocoa--Trinidad and Tobago; Cocoa processing--Trinidad and Tobago; Working class--Trinidad and Tobago; Cocoa houses